Membangun Sikap Kerja Profesional Karyawan Anara Airport Hotel Tangerang - Surahman Pujianto; Erika Jimena Arilyn; Ian Nurpatria Suryawan; Wibisono Soediono (Indonesia Berdaya, 2023)
Community service activities include increasing the speed of community development efforts towards fostering a harmonious and dynamic society that is ready to take chances towards improvement and progress in accordance with socio-cultural values and norms in the life of a developing community in the life of the prevailing society. This training uses an explanatory case study approach to explain various case studies of the professional work attitudes of Anara Airport Hotel employees. The main activities of the training besides presentation and explanation of the material, a simple assessment of the professional work attitude of employees is also carried out, namely the FGD (focus group discussion) method and case studies. Abstrak: Kegiatan pengabdian kepada masyarakat beberapa diantaranya adalah bertambahnya kecepatan upaya pengembangan masyarakat ke arah terbinanya masyarakat yang harmonis serta dinamis yang siap menempuh perubahan-perubahan menuju perbaikan dan kemajuan sesuai dengan nilai-nilai sosial budaya dan norma-norma dalam kehidupan masyarakat berkembang dalam kehidupan masyarakat yang berlaku. Pelatihan ini menggunakan pendekatan studi kasus eksplanatori untuk menjelaskan berbagai studi kasus sikap kerja profesional karyawan Anara Airport Hotel. Aktivitas utama pelatihan selain presentasi dan penjelasan materi, juga dilakukan asesmen sederhana atas sikap kerja professional kerja para karyawan, yakni dengan metode FGD (focus group discussion) dan studi kasus.